The Incoming Mail Management System Design and Exit at the General Bureau of the Web Based Governor's Office - Maulida, Dzikra; Siregar, Nora Arianti; Hasugian, Abdul Halim (Unity Academy, 2023)
Incoming mail archiving is still stored in a general ledger sorted by date and the incoming mail filing process only stores mail files in the general ledger so that if the mail file is lost and if the file is needed again, the mail will be difficult to find. The method used to design the Correspondence Management Information System is the waterfall method. The result is a data processing system that can be run properly. Thus it can be known whether this software can produce information system applications that are in accordance with the expected goals. With the design of this application, it is expected to facilitate the company in the process of collecting correspondence starting from the identity of the letter, the time of receipt of the letter to the destination of the letter.